The development of quality management in Thailand - Krasachol, Ladawan (1999)
This thesis presents the results of an investigation into the development of quality management in Thailand. The research was conducted in order to draw up an overall picture of quality progress in Thai industry, to provide useful insights for Thai companies and policy-makers, as well as to compare Thailand with other developing countries.